The effect of microwave heating on the microstructure and the mechanical properties of reaction‐bonded boron carbide. Issue 2 (18th September 2019) - Dutto, Mathieu; Goeuriot, Dominique; Saunier, Sébastien; Sao‐Joao, Sergio; Marinel, Sylvain; Frage, Nachum; Hayun, Shmuel
Abstract: Reaction‐bonded boron carbide composites were fabricated by both microwave (under Ar/10% H2 ) and conventional heating (under vacuum or Ar/10% H2 ). Silicon carbide (SiC) formation occurred in all cases and was slightly favored in the case of microwave heating under Ar/H2 . The resulting microstructures were influenced by the heating process and atmosphere; the SiC existed in the form of needles with conventional heating under vacuum. SiC small polygonal grains were present after microwave heating under Ar/H2 . Both the atmosphere and the electromagnetic field influence the SiC morphology. Despite this difference, the hardness and toughness of composites obtained by both heating techniques were similar.